PERKEMBANGAN PENDIDIKAN DAN PEMBELAJARAN ERA SOCIETY 5.0 - Anis Sukmawati; Ghina Zayyina Amalia Mozamb; Inggit Delia Zulfa (Universitas Islam Negeri Sumatera Utara Medan, 2023)
The Development of education and learning continues to change over time with technological advancements in the era of society 5.0. The emergence of a new civilization that underwent development from the previous revolution, namely the industrial era 4.0 which experienced development into the era of society 5.0 surprised all sectors including the world of education. This era is characterized by increasingly strong integration between people and technology, where intelligence AI, IoT and other technologies play an important role in the transformation of society and the education system. The purpose of this scientific paper is to analyze the impact and social changes that arise along with this development. The results of this study provide insight for education practitioners and other parties to develop appropriate strategies and policies in dealing with developments in education and learning in the era of society 5.0. collaboration between government, educational institutions, industry and society is needed to ensure inclusive technology, privacy protection, adequate skills preparation to face an increasingly connected future.Â Â Keywords: New Civilization, Education, Learning, Society 5.0